Adsorption of Vitamin K-dependent Proteins to Live Cell Membranes Measured under Flow Conditions - McGee, Maria P.; Teuschler, Hoa (Thrombosis and Haemostasis, 1999)
Mechanisms mediating initial adsorption of coagulation proteins to live cells were investigated. Adsorption kinetics were examined under varying flow conditions using tracer-dilution techniques in perfused spherical monolayers of cells expressing tissue factor. At biologically relevant time and concentration ranges, rates exceeded by 2-12 fold the theoretical maximum calculated for steady-state diffusion. Rates were correlated with aqueous-phase flux of reactants and were found to be largely independent of the density of reactive sites on the membrane. Average adsorption rate of factor VIIa at 4 ηM and flow velocity of 0.8 ηm s-1 was 5 × 107 s-1 cm-2. Adsorption rates of homologous coagulation factors IX and X under similar conditions were 5 and 9 × 107 s-1 cm-2. Results indicate that flow can effectively increase the rate of coagulation factor adsorption to the membrane of live cells. They also imply that factors affecting blood flow velocity and vessel permeability influence the rate of membrane-dependent coagulation reactions.